Make It All About Them : Winning Sales Presentations. - Keller, Nadine (Wiley, 2012)
Debunks the myths of the traditional rules of presentations In today's commodity-based marketplace it is harder than ever to differentiate even the most superlative services and products. The sales presentation provides the most powerful opportunity to do so. Make It All About Them reveals the truth behind the traditional rules of presentations and offers sales professionals a new way forward. It explains why focusing on three key points trumps a presentation full of details, why plain English always wins over jargon, why the audience doesn't need to know how important you are.